2015
DOI: 10.1590/1983-80422015232069
|View full text |Cite
|
Sign up to set email alerts
|

A relação médico-paciente sob a influência do referencial bioético da autonomia

Abstract: Objetivo analisar a influência do referencial bioético da autonomia na relação médico-paciente, o efeito da internet nessa autonomia e a importância dessa relação frente avanços tecnológicos.Método estudo com técnica descritiva e exploratória, utilizando abordagem quantitativa e qualitativa.Resultados 10% viram o surgimento do referencial da autonomia como o fator mais importante nas mudanças da relação; 96% consideraram a introdução da autonomia importante ou muito importante; 84% declararam que ela torna a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…It is also argued that secrecy is associated with the bioethical principle of autonomy (19) , because personal data belongs solely and exclusively to the patient, who is the only one who can decide with whom this information may be shared. In this sense, health professionals, who are familiar with the data and information of users, should not disclose it, unless authorized by the user or in exceptional situations, as indicated by ethics or the law, such as cases of required reporting stipulated by law and regulations, where professionals may break secrecy covenants due to epidemiological criteria related to public health (18,20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also argued that secrecy is associated with the bioethical principle of autonomy (19) , because personal data belongs solely and exclusively to the patient, who is the only one who can decide with whom this information may be shared. In this sense, health professionals, who are familiar with the data and information of users, should not disclose it, unless authorized by the user or in exceptional situations, as indicated by ethics or the law, such as cases of required reporting stipulated by law and regulations, where professionals may break secrecy covenants due to epidemiological criteria related to public health (18,20) .…”
Section: Discussionmentioning
confidence: 99%
“…The concept of autonomy is associated with the progressive consolidation of human rights. It was incorporated into the doctor-patient relationship more precisely in the 1960s, based on empirical studies that showed an association between greater support for the autonomy of patients and better health outcomes (19) . However, the democratization of the relationship between health professionals and patients, the importance of the autonomy of patients in therapy choices and procedures to be followed, and models in which patients and physicians are seen as jointly responsible in this process, are practices still in the early stages (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Many who idealize it do so for unconscious motivations and as an attempt to cease some type of preexisting suffering. In general, the impossibility of facing external or internal pressures can affect self-determination 18 and rationality 19 , intensifying suicidal ideation.…”
Section: Autonomymentioning
confidence: 99%
“…33,34 A autonomia está associada à consolidação de direitos humanos e no contexto da relação médico-paciente está associada ao respeito e reconhecimento da pessoa como capaz de influenciar o seu cuidado e, assim de forma compartilhada, alcançar a opção mais adequada ao seu contexto de vida. 35 Estudos internacionais apresentam resultados semelhantes a esse estudo no que se refere à vontade dos pacientes de serem incluídos na decisão, no entanto, apresentam barreiras individuais e estruturais do sistema de saúde. [36][37][38] Implicações para a prática profissional…”
Section: Valorização Da Autonomia Dos Homens Na Tomada De Decisão Clínicaunclassified